Effective mass anisotropy of Si-Ge alloys: a discussion of the effective mass tensor. (14th October 2020) - Song, Yanxing; Chai, Changchun; Fan, Qingyang; Zhang, Wei; Yang, Yintang
Abstract: In this work, the stability, mechanical properties, mechanical anisotropy properties, electronic properties and effective mass anisotropy of C 2/ m -20 Si1- x Ge x ( x  = 0, 0.2, 0.4, 0.6, 0.8, 1) are studied through ab initio calculations. Effective mass is an important index to measure the transport properties of semiconductor. The analysis of effective mass anisotropy can provide theoretical basis for the design of crystal orientation of semiconductor devices. By increasing the discussion of the differentiability of the E - k relation of carriers, the rationality of its Taylor expansion is determined to judge the feasibility of the effective mass tensor. Avoiding the misuse of the effective mass tensor enables researchers to obtain more accurate and reliable results in the analysis of the effective mass anisotropy. Through the combination of the effective mass tensor method and the traversal method, the lowest effective mass can be quickly found while the amount of calculation is greatly reduced. This is of great significance for research on the carrier transport properties of materials. Extremely low hole effective masses is found in a novel phase of germanium with a hole effective mass of 0.017 m 0 in [001] direction. This indicates that C 2/ m -Ge20 has a very high carrier mobility in [001] direction which have a great impact on the field of electronic devices.